Performance Comparison of Internet Service from Best Telecom ETL Unitel and Laotelecom at Souphanouvong University - SENGDALA, Sinlapaxay; VONGSAVANH, Amphai; MEKSAVANH, Bounhome; VILAYSACK , Bounthanome; THIPPHAVANH, Phoneouthai (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Currently, the provision of Internet services by different providers varies in terms of performance due to differences in operational capabilities and certain functional limitations. This research aims to compare the performance of Internet services from four providers: Best Telecom, ETL, Unitel, and LaoTelecom. The evaluation was conducted at Souphanouvong University between October and November 2023. The tests included pinging both domestic and international websites, screening, bandwidth speed tests, and FTP download/upload tests. The results showed that ETL demonstrated the best ping performance at 36 ms and had the most efficient broadcasting capabilities. LaoTelecom achieved the highest FTP download and upload speeds, with 21.239 kbps and 21.786 kbps, respectively. The performance of Best Telecom and Unitel was at a moderate level across most test categories.